ANALISIS PENGARUH LIKUIDITAS, CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, DAN PERTUMBUHAN PENDAPATAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR TAHUN 2019 – 2023 - Hesti Ning Tyas, Hesti Ning Tyas; Hwihanus , Hwihanus (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze the influence of liquidity, Corporate Social Responsibility (CSR), leverage, and revenue growth on financial performance and profit margins in manufacturing companies in Indonesia during the 2020-2024 period. Research data was obtained from financial reports of companies listed on the Indonesia Stock Exchange (BEI) and processed using SmartPLS. The independent variables in this research include liquidity, CSR, and leverage, while revenue growth acts as a mediating variable. Financial performance and profit margin are used as dependent variables. The research results show that liquidity and CSR have a significant positive influence on revenue growth and company financial performance. On the other hand, leverage has a negative influence on financial performance, indicating that high levels of debt can hinder a company's ability to generate profits. Revenue growth acts as a significant mediator in the relationship between liquidity, CSR, and leverage on financial performance. In addition, financial performance is proven to have a significant direct influence on profit margins, which emphasizes the importance of optimal financial management to increase profitability. This research emphasizes the importance of liquidity management, strategic CSR implementation, and careful leverage management in supporting company revenue growth, financial performance and profitability. It is hoped that these findings will provide insight for company management in formulating strategies to increase competitiveness and business sustainability.